2016
DOI: 10.1371/journal.pone.0163312
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Yeast Peptidome and Comparison with the Human Peptidome

Abstract: Peptides function as signaling molecules in species as diverse as humans and yeast. Mass spectrometry-based peptidomics techniques provide a relatively unbiased method to assess the peptidome of biological samples. In the present study, we used a quantitative peptidomic technique to characterize the peptidome of the yeast Saccharomyces cerevisiae and compare it to the peptidomes of mammalian cell lines and tissues. Altogether, 297 yeast peptides derived from 75 proteins were identified. The yeast peptides are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 63 publications
3
58
0
2
Order By: Relevance
“…These studies also demonstrated that the overexpression of THOP1, which has been shown to be involved in the metabolism of specific intracellular peptides [53] and modulation of signal transduction of angiotensin II (AT1) and β-adrenergic GPCR in CHO and HEK293 cells. Recent studies in HEK293 cells showed that most of these intracellular peptides are generated by the proteasome, where additional intracellular peptide-generating peptidases also exist [52,[54][55][56].…”
Section: Brief Historical Perspective On Proteasome-derived Intracellmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies also demonstrated that the overexpression of THOP1, which has been shown to be involved in the metabolism of specific intracellular peptides [53] and modulation of signal transduction of angiotensin II (AT1) and β-adrenergic GPCR in CHO and HEK293 cells. Recent studies in HEK293 cells showed that most of these intracellular peptides are generated by the proteasome, where additional intracellular peptide-generating peptidases also exist [52,[54][55][56].…”
Section: Brief Historical Perspective On Proteasome-derived Intracellmentioning
confidence: 99%
“…Different treatments and/or diseases modify the relative concentration of specific intracellular peptides present inside the cells and tissues, suggesting pathophysiological functions [51,54,55]. In challenge conditions, cells start accumulating or losing specific intracellular peptides that are biologically functional in such conditions.…”
Section: Brief Historical Perspective On Proteasome-derived Intracellmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our group developed a substrate-capture assay using a catalytically inactive form of thimet oligopeptidase (EC 3.4.24.15, EP24.15; THOP1) that allowed for the seminal identification of mammalian intracellular peptides, which are products of proteasome activity distinct from MHC-I antigens [9,10]. To date, multiple research groups have identified hundreds of novel intracellular peptides in human cell lines [11,12], human tissues [13,14], rodents [15,16], zebrafish [17], yeast [18], and plants [19,20]. THOP1 only hydrolyzes a restricted group of peptides in the optimal range of 8-12 amino acids in length [21][22][23], and has never been shown to degrade proteins, likely due to its catalytic site being deeply located in the bottom of a narrow channel [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the formation of AtRALF1 and AtRALF23 peptides depends on precursor cleavage by subtilisin‐like proteinase S1P/SBT6.1 (serine‐type), and phytaspases (aspartic‐type) were shown to cleave prosystemin in tomato . In addition, proteasomes, which have caspase‐like, trypsin‐like, and chymotrypsin‐like activities, can be responsible for the generation of peptide pools in animal cells . However, it is not known whether proteasomes influence peptide pools in plant cells and secretomes.…”
Section: Introductionmentioning
confidence: 99%